A comprehensive wealth index for cities in Germany - Dovern, Jonas; Quaas, Martin F.; Rickels, Wilfried (Ecological indicators, 2014)
We apply a comprehensive wealth index for the 100 largest autonomous cities in Germany to measure their endowment with environmental, energy, social, human, and economic capital stocks. We find that (i) there is no inherent trade-off between economic and environmental capital stocks; (ii) clear regional differences exist between West and East Germany and between North and South Germany; and (iii) the comprehensive wealth index is strongly correlated with housing rents, which reflect individual willingness to pay for living in a certain city.